STRATEGIC DIRECTIONS OF VOCATIONAL EDUCATION DEVELOPMENTIN THE CONTEXT OF EUROPEAN INTEGRATION (Innovative professional education, 2024)
The sub-section highlights the directions of implementation of the EU socio-economic development strategy adopted by the European Council. The dynamics and mechanism of interaction of the three main priorities of modern socio-economic development are considered. The conclusion is made that creative implementation of such a strategy in Ukraine will create an opportunity for more dynamic progress towards achieving the innovative, educational and intellectual competitiveness of our country.
Keywords: strategy, vocational education, sustainable development, stable future, modernization, professional growth, innovation policy